The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13046-020-01798-2
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs regulate alternative splicing in Cancer

Abstract: AS (alternative splicing) is a fundamental process by which a gene can generate multiple distinct mRNA transcripts to increase protein diversity. Defects in AS influence the occurrence and development of many diseases, including cancers, and are frequently found to participate in various aspects of cancer biology, such as promoting invasion, metastasis, apoptosis resistance and drug resistance. NcRNAs (noncoding RNAs) are an abundant class of RNAs that do not encode proteins. NcRNAs include miRNAs (microRNAs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 137 publications
(152 reference statements)
0
71
0
1
Order By: Relevance
“…AS mainly relies on splice bodies, splice sites, cis-acting elements, and trans-acting factors to participate in the proliferation, invasion, chemotherapy resistance, and apoptosis of various cancers. 67 A variety of circRNAs containing exons or introns can be generated by a single gene through alternative splicing. A large number of studies have found that circRNAs are covalently linked to upstream and downstream-specific splicing sites generated from standardized sequences in pre-mRNA or nonstandardized reverse splicing sequences that have potential for gene regulation.…”
Section: Circrnas and Alternative Splicingmentioning
confidence: 99%
“…AS mainly relies on splice bodies, splice sites, cis-acting elements, and trans-acting factors to participate in the proliferation, invasion, chemotherapy resistance, and apoptosis of various cancers. 67 A variety of circRNAs containing exons or introns can be generated by a single gene through alternative splicing. A large number of studies have found that circRNAs are covalently linked to upstream and downstream-specific splicing sites generated from standardized sequences in pre-mRNA or nonstandardized reverse splicing sequences that have potential for gene regulation.…”
Section: Circrnas and Alternative Splicingmentioning
confidence: 99%
“…Noncoding RNAs (ncRNAs) participate in all aspects of cancer biology, such as cell apoptosis, proliferation and drug resistance [5] . Circular RNAs (circRNAs) are covalently closed-loop ncRNAs without 5′ and 3′ ends, and they are produced by back-splicing of premessenger RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many AS changes have been found to play an important role in the development of cancer. With the development of high-throughput sequencing and RNA-seq techniques, thousands of non-coding RNAs have been identified as critical for regulating AS at multiple levels in cancer ( 28 ). LncRNA DGCR5 binds directly to serine-and arginine-rich splicing factor 1(SRSF1) to increase its stability, thereby stimulating the Mcl-1 alternative splicing event to promoting the occurrence of esophageal squamous-cell carcinoma in vivo ( 29 ).…”
Section: Function Of Lncrnas In Gastrointestinal Cancermentioning
confidence: 99%